2015
DOI: 10.5301/jva.5000467
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Techniques for Haemodialysis Access-Induced Distal Ischaemia

Abstract: All four procedures have high success rate in relieving ischaemic symptoms with the DRIL procedure having a significantly better vascular access patency rate than other techniques, although further well designed studies are required to compare all four surgical techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…In line with the current survey, patients identified that care could be improved by encouraging collaborative decision-making between the clinician and the patient. Similarly, Larsen et al [ 32 ] found, in a cohort of 10 medical/surgical patients, that these patients reported communication breakdowns between the inserter and themselves and that this was a cause for concern. These patients were keen to suggest areas for improvement, including insertion techniques, insertion site choice and ways to increase comfort and reduce anxiety, which suggests that they are keen to be more active participants in their care.…”
Section: Discussionmentioning
confidence: 94%
“…In line with the current survey, patients identified that care could be improved by encouraging collaborative decision-making between the clinician and the patient. Similarly, Larsen et al [ 32 ] found, in a cohort of 10 medical/surgical patients, that these patients reported communication breakdowns between the inserter and themselves and that this was a cause for concern. These patients were keen to suggest areas for improvement, including insertion techniques, insertion site choice and ways to increase comfort and reduce anxiety, which suggests that they are keen to be more active participants in their care.…”
Section: Discussionmentioning
confidence: 94%
“…7d). 602 The proximal bypass anastomosis should be placed at least 10 cm above the VA anastomosis to ensure adequate deviation of sufficient flow to the distal extremity. In RCAVFs with ischaemia, ligation of the distal limb of the radial artery may be an alternative (Fig.…”
Section: Recommendation 64mentioning
confidence: 99%
“…7f). 602,603 HD patients with VA flow > 1500 ml/min should be monitored regularly by flow measurements, echocardiography and for clinical signs of congestive heart failure (CHF). Patients with progression of symptoms, progressive increase in VA flow or objective signs of heart failure should be considered for the surgical procedures described above.…”
Section: Recommendation 64mentioning
confidence: 99%
“…In that case, superficialization on a deep brachial vein is possible, but the primary and secondary flow of such vascular access is insufficient. In addition, an aneurysm at the puncture site for hemodialysis, axillary vein thrombosis, "steal syndrome, " and other complications are frequent [13]. It is well known that implantation of the vascular graft requires appropriate diameter and quality of arterial and venous blood vessels, which may be a major obstacle for this type of surgery [14].…”
Section: Discussionmentioning
confidence: 99%